04.14 Aortic valve disease co-develops with polyarthritis in the tnf-driven models and shares a common mesenchymal cell-mediated causality. (1st March 2017) - Ntari, Lydia; Sakkou, Maria; Chouvardas, Panagiotis; Prados, Alejandro; Katevaini, Anna; Karagianni, Niki; Denis, Maria C; Kollias, George
Abstract : Introduction and objectives: Rheumatoid arthritis (RA) is a chronic condition characterised by inflammation of the joints as well as destruction of bone and cartilage. Studies on TNF transgenic models of polyarthritis established Tumour Necrosis Factor (TNF) targeting the mesenchymal-origin Synovial Fibroblasts (SFs) as a key event instigating the pathology. RA patients often show higher mortality rates, mainly due to the development of extraarticular disease including cardiovascular, gut and skin manifestations. The Tg197 and Tnf ΔARE/+ mouse models overexpress TNF and develop spontaneous chronic polyarthritis, fully mimicking human RA pathology. Here, we investigate whether these models develop, similarly to human patients, co-morbid heart pathology. Materials and methods: We used the Tg197 and Tnf ΔARE/+ mouse models to evaluate possible arthritis-related cardiovascular disease. For further ex vivo analysis, we isolated Valve Interstitial Cells (VICs), which are the mesenchymal-origin fibroblasts constituting the aortic valve. We used a GFP reporter mouse labelling specifically mesenchymal-origin cells (ColVICre;mTm/mGFP) to target VICs. Similarities of pathogenic VICs and SFs were analysed by comparing their expression profiling with RNA sequencing analysis. Results: Both arthritis models examined develop TNF-dependent aortic valve thickening, as indicated by the amelioration of the pathology following treatment with anti-TNF biologics. Aortic valves exhibited significant fibrosis with minimal signs of inflammatory cell infiltration and thickened areas, consisting almost entirely of VICs, indicating proliferation of this cell type as a hallmark of the observed phenotype. Isolated VICs from mutant mice exhibited a more proliferative and migratory phenotype and expressed high levels of TNF. Interestingly, VIC activation resembles the activated phenotype of pathogenic SFs isolated from the same mice. A significant functional correlation between these two pathogenic cells of mesenchymal origin was also supported by RNA-seq analysis, suggesting common cellular mechanisms operating in RA and RA-related heart pathology. Conclusion: TNF-driven arthritis models, apart from their arthritic symptoms, develop co-morbid heart valve disease, similarly to reported comorbidities in RA patients. These two co-morbid diseases are shown here to share common mesenchymal-cell driven aetiopathogenesis.